The bivalves (Mollusca) from Priority Marine Regions in the centre-south of the Mexican Transitional Pacific, associated with the rocky intertidal zone - Victor I. López-Rojas; Carmina Torreblanca-Ramírez; Jesús G. Padilla-Serrato; Pedro Flores-Rodríguez; Rafael Flores-Garza (Nature Conservation Research: Заповедная наука, 2023)
In Mexico, due to its high biological diversity, use of its resources, and a lack of knowledge about its biodiversity, Priority Marine Regions have been designated. The classification of these regions has served as an instrument for the large-scale conservation because the species composition is relatively homogeneous in these regions. This study reports some ecological attributes of bivalves from the Priority Marine Regions located in the Mexican Transitional Pacific ecoregion. Three samplings have been carried out in 2016–2018 in the rocky intertidal zone. In each sample per site, an area of 10 m2 was covered, and the sampling unit was 1 m2. A total of 4119 specimens were recorded, by identifying 53 species (35 genera, 18 families, and two specimens identified to genus). The richness of the species expected was calculated using non-parametric estimators, by showing acceptable completeness of the inventory. The highest species richness and diversity were recorded in the Copala-Punta Maldonado region (33 species), whereas the highest abundance and density were found in the Colola-Maruata region (30.9 individuals/m2). The best-represented species in abundance and distribution were Chama coralloides, Brachidontes adamsianus, Isognomon janus, and Choromytilus palliopunctatus. By considering their life form and degree of occurrence, studied bivalves attached to a hard substrate (epifaunal species) and restricted to habitats with particular characteristics (occasional species) were the most commonly found. The information provided here is directed to eight Marine Regions designated as a priority for conservation in Mexico, which is important for planning, decision-making, and formulating initiatives aimed at helping to co-ordinate management practice through outreach efforts to the conservation and sustainable use of bivalves as marine resources.